2000
DOI: 10.5511/plantbiotechnology.17.87
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of p-Hydroxybenzyl Alcohol on Somatic Embryogenesis in Carrot Cell Cultures.

Abstract: Somatic embryogenesis in carrot (Daucus carooa L.) is strongly inhibited by certain factors that accumulate in the medium of cultures with high embryogenic carrot cell density. We previously identified p -hydroxybenzyl alcohol as one of these inhibitory factors. In this study, we performed a detailed analysis of the effects of p -hydroxybenzyl alcohol on somatic embryogenesis. p -Hydroxybenzyl alcohol strongly inhibited the formation of somatic embryos by suppressing cell division. The inhibitory effect on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…1). We previously showed that exogenous application of authentic 4HBA at 1.0×10 −7 M strongly inhibits somatic embryogenesis and the inhibitory effect of 4HBA is strong on the development of early globular embryos (Kobayashi et al 2000b). Therefore, the rapid accumulation of 4HBA in high cell density cultures during the early stages might cause the strong suppression of somatic embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). We previously showed that exogenous application of authentic 4HBA at 1.0×10 −7 M strongly inhibits somatic embryogenesis and the inhibitory effect of 4HBA is strong on the development of early globular embryos (Kobayashi et al 2000b). Therefore, the rapid accumulation of 4HBA in high cell density cultures during the early stages might cause the strong suppression of somatic embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…3). On the other hand, the inhibitory effect of 4HBA was strong during the development of early globular embryos (Kobayashi et al 2000b). The early globular stages of somatic embryogenesis are important for differentiation and pattern formation in somatic embryos (Fujimura and Komamine 1980; Dudits et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An inhibitory factor isolated from the medium was firstly characterized as a 4-hydroxybenzyl alcohol (4HBA; Kobayashi et al 2000a). 4HBA accumulated rapidly in the medium and specifically inhibits rapid cell division during the early globular stage of somatic embryogenesis (Kobayashi et al 1999b(Kobayashi et al , 2000b(Kobayashi et al , 2001. While 4HBA inhibits embryogenesis in carrot, this factor does not inhibit somatic embryogenesis in several other species including Japanese larch (data not shown).…”
Section: Inhibitory Factors That Modulate Somatic Embryogenesismentioning
confidence: 99%